Acute peripheral inflammation does not change cerebral glucose metabolism. (31st December 2021) - Machado, Luiza Santos; dos Santos, Camila N.; da Rocha, Andreia Silva; Fontana, Igor C.; Bellaver, Bruna; Leonardi, Bianca F.; Venturin, Gianina Teribele; Greggio, Samuel; da Costa, Jaderson Costa; Zimmer, Aline R.; Zimmer, Eduardo R.
Abstract: Background: Neuroinflammation is a phenomenon already described in the brain of Alzheimer's disease (AD) individuals, with sustained neuroinflammatory response being detrimental. The effect of peripheral inflammation in AD is less understood. In fact, central nervous system (CNS) is protected from peripheral inflammation by the blood‐brain barrier. However, we recently demonstrated that severe sepsis causes acute brain metabolic disturbances, evidencing the CNS invasion of inflammatory mediators may affect brain function. Nevertheless, whether mild acute peripheral inflammation affects brain metabolism remains unclear. Objective: Here, we aimed at investigating the impact of mild acute peritonitis on brain energetic metabolism. Hypothesis: We hypothesized that mild peripheral inflammation will cause widespread brain glucose hypometabolism. Method: Adult male Wistar rats were randomly separated into carrageenan group, a model of mild acute peripheral inflammation (n=6), and control group (n=6). Peritonitis was induced by the administration of 500 µg of intraperitoneal (i.p.) carrageenan, while the control group was i.p. injected with 500 µl of saline. In vivo cerebral glucose metabolism was assessed using ( 18 F)FDG‐microPET 4 h after inflammatory induction, which represents the first peak of inflammation. The peripheral inflammatory process was evaluated by analyzing the peritoneal lavage in a Flow Cytometer 48 h after the scanning i.p. injections, the second of peak of inflammation, Result: The animals treated with carrageenan presented a 5‐fold increase in macrophages numbers (p<0, 05) and a 2‐fold increase in monocytes numbers (p>0, 05). However, our data showed that carrageenan‐induced peripheral inflammation did not cause acute changes in the whole brain glucose metabolism (p>0, 05). Further regional analysis, in frontal and temporoparietal cortices, striatum, hippocampus, cerebellum, thalamus and hypothalamus, did not identify any difference between groups. Conclusion: Mild acute peripheral inflammation does not change brain glucose metabolism. Further evaluation aiming to investigate long‐term consequences of sustained mild inflammation are needed.